DARTOS FASCIA AS AN INTERPOSITIONAL LAYER IN HYPOSPADIAS URETHROPLASTY: A SYSTEMATIC REVIEW - Marta Hendry; Krisna Murti; Besut Daryanto; Iche Andriyani Liberty (Indonesian Urological Association, 2026)
Introduction: Hypospadias is a common congenital anomaly of the male genitalia (1 in 300 births), characterized by a ventrally displaced meatus, often with chordee and a dorsal hooded prepuce. Objective: This systematic review evaluated the role of dartos fascia as an interpositional layer in primary hypospadias repair. Material & methods: Search was conducted in PubMed, EMBASE, Scopus, CENTRAL, and Web of Science (2019–2025) for studies in patients ≤18 years undergoing hypospadias repair. Primary outcomes were urethrocutaneous fistula (UCF), dehiscence, meatal/urethral stenosis, and reoperation; secondary outcomes were infection and cosmetic scores. Narrative synthesis was used. Results: Eleven studies met criteria, predominantly distal TIP. No randomized trial compared any second layer versus none; one cohort (n=425) showed similar UCF with periurethral/dartos coverage versus none (6.7% vs 7.3%). A randomized trial favored double- over single-layer dartos (3.3% vs 23.3%). Another trial found ventral preferable to dorsal dartos with fewer flap-related complications at similar UCF rates. Tunica vaginalis flap reduced UCF and improved cosmetics but is more invasive. Platelet-rich fibrin adjunct lowered UCF and infection in two studies. Spongioplasty produced comparable UCF but higher meatal stenosis, though selected robust spongiosum allowed zero fistulas. Conclusion: Dartos remains the workhorse; double-layer and ventral harvest optimize outcomes, while tunica vaginalis and PRF offer effective alternatives in selected cases. Further randomized trials are needed to clarify the necessity of a second layer. Keywords: Hypospadias, urethroplasty, dartos fascia, urethrocutaneous fistula, tunica vaginalis flap.